ANALISIS KINERJA APBD DENGAN PENGUKURAN VALUE FOR MONEY PEMERINTAH KOTA MALANG (TAHUN PERIODE 2011-2015) - Ulfa, Evi Indana; Made, Anwar; Dianawati, Eris (Jurnal Riset Mahasiswa Akuntansi, 2018)
This study aims to analyze to find out how to measure the effectiveness of the Malang City's APBD (Local Government Budget), to find out whether the Malang City's APBD (Local Government Budget) is quite effective and to find out how to measure the Malang City Government's accounting effectiveness. This research uses quantitative research methods. The data used in this study are secondary data, that is data already available from official documents of the Malang city government. Data collection techniques used by researchers is by logging data. Results of research The effectiveness level of Malang City's APBD (Local Government Budget) in 2011-2015 was very effective, because the average was 103.27 percent, greater than the specified criteria, which is at least 90 percent, the level of efficiency of the Malang City's APBD (Local Government Budget) in 2011-2015 was less efficient, because it was average -The rate of 105.26 percent is greater than the specified criteria, which is a maximum of 80 percent, when viewed from how much the proportion of PAD can contribute to regional income, the level of financial capability of the Malang City Government in 2011-2015 is less able, because on average 13.03 percent is far less than the specified criteria, which is a minimum of 40 percent and when viewed from how much PAD can sustain regional spending, the level of financial capability of Malang City Government in 2011 - 2015 is less able, because the average is 12.17 percent smaller than the specified criteria, which is a minimum of 40 percent.